Auditory and Cognitive Factors Associated with Speech-in-Noise Complaints following Mild Traumatic Brain Injury - Hoover, Eric C.; Souza, Pamela E.; Gallun, Frederick J. (Journal of the American Academy of Audiology, 2017)
Background: Auditory complaints following mild traumatic brain injury (MTBI) are common, but few studies have addressed the role of auditory temporal processing in speech recognition complaints.Purpose: In this study, deficits understanding speech in a background of speech noise following MTBI were evaluated with the goal of comparing the relative contributions of auditory and nonauditory factors.Research Design: A matched-groups design was used in which a group of listeners with a history of MTBI were compared to a group matched in age and pure-tone thresholds, as well as a control group of young listeners with normal hearing (YNH).Study Sample: Of the 33 listeners who participated in the study, 13 were included in the MTBI group (mean age = 46.7 yr), 11 in the Matched group (mean age = 49 yr), and 9 in the YNH group (mean age = 20.8 yr).Data Collection and Analysis: Speech-in-noise deficits were evaluated using subjective measures as well as monaural word (Words-in-Noise test) and sentence (Quick Speech-in-Noise test) tasks, and a binaural spatial release task. Performance on these measures was compared to psychophysical tasks that evaluate monaural and binaural temporal fine-structure tasks and spectral resolution. Cognitive measures of attention, processing speed, and working memory were evaluated as possible causes of differences between MTBI and Matched groups that might contribute to speech-in-noise perception deficits.Results: A high proportion of listeners in the MTBI group reported difficulty understanding speech in noise (84%) compared to the Matched group (9.1%), and listeners who reported difficulty were more likely to have abnormal results on objective measures of speech in noise. No significant group differences were found between the MTBI and Matched listeners on any of the measures reported, but the number of abnormal tests differed across groups. Regression analysis revealed that a combination of auditory and auditory processing factors contributed to monaural speech-in-noise scores, but the benefit of spatial separation was related to a combination of working memory and peripheral auditory factors across all listeners in the study.Conclusions: The results of this study are consistent with previous findings that a subset of listeners with MTBI has objective auditory deficits. Speech-in-noise performance was related to a combination of auditory and nonauditory factors, confirming the important role of audiology in MTBI rehabilitation. Further research is needed to evaluate the prevalence and causal relationship of auditory deficits following MTBI.
Keywords: auditory processing disorder; hearing impairment; postconcussive syndrome; traumatic brain injury